THE LEGAL RESPONSIBILITY OF DEBTOR TO PAYMENT CURATORS IN BANKRUPTCY SITUATION - Didi Sukardi (UNISSULA, 2021)
The Law on Bankruptcy and the Obligation to Postpone Debt Payment does not explicitly stipulate that the obligation to pay the Curator's fee is borne by the Applicant, the Debtor or the Applicant and the Debtor jointly. The obligation to pay the curator fee is imposed through the determination of the Court of Judges who decides the bankruptcy case on the Curator's Application based on the details submitted by the Curator after hearing the considerations of the Supervisory Judge. The approach method used is a normative juridical approach the curator fees. according to Act No. 37 of 2004 concerning Bankruptcy and the Obligation to Postpone Debt Payment is not absolute, because the obligation to pay the Curator's fee can be imposed on the Applicant for the Declaration of Bankruptcy, the Bankrupt Debtor, or on the Petitioner for the Declaration of Bankruptcy and the Debtor for Bankruptcy jointly through the Determination of the Panel of Judges who decides the Bankruptcy Application.